A longitudinal study of ammonia, acetone and propanol in the exhaled breath of 30 subjects using selected ion flow tube mass spectrometry, SIFT-MS - Turner, Claire; Španěl, Patrik; Smith, David (Physiological measurement, 2006)
Selected ion flow tube mass spectrometry, SIFT-MS, has been used to monitor the volatile compounds in the exhaled breath of 30 volunteers (19 males, 11 females) over a 6 month period. Volunteers provided breath samples each week between 8:45 am and 1 pm (before lunch), and the concentrations of several trace compounds were obtained. In this paper the focus is on ammonia, acetone and propanol. It was found that the concentration distributions of these compounds in breath were close to log-normal. The median ammonia level estimated as a geometric mean for all samples was 833 parts per billion (ppb) with a multiplicative standard deviation of 1.62, the values ranging from 248 to 2935 ppb. Breath ammonia clearly increased with increasing age in this volunteer cohort. The geometric mean acetone level for all samples was 477 parts per billion (ppb) with a multiplicative standard deviation of 1.58, the values ranging from 148 to 2744 ppb. The median propanol level for all samples was 18 ppb, the values ranging from 0 to 135 ppb. A weak but significant correlation between breath propanol and acetone levels is apparent in the data. The findings indicate the potential value of SIFT-MS as a non-invasive breath analysis technique for investigating volatile compounds in human health and in the diseased state.